Fear in the Perspective of the Qur’an and Hadith: Semantic, Theological, and Spiritual Analysis of Khauf, Khasyyah, and Rahbah - Rusdina Rusdina; Mahyuddin Barni; Abdul Basir; Ali Muammar (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the concept of “fear” from the perspective of the Qur’an and Hadith through semantic, theological, and spiritual analysis, focusing on the terms khauf, khasyyah, and rahbah. The study reveals that fear in Islam is not merely an emotional reaction but a multidimensional spectrum with moral, spiritual, and social functions. Khauf represents basic fear of punishment and sin, rahbah reflects fear combined with spiritual longing, while khasyyah is a transcendental fear arising from knowledge and reverence of Allah. This hierarchy forms the structure of a servant’s spiritual journey from self-awareness to divine consciousness. The findings highlight that balanced fear promotes sincere obedience, self-discipline, and spiritual maturity, whereas misinterpretation can lead to extremism. Understanding the concept of fear correctly is essential for fostering moderate and harmonious Islamic spirituality.